Examining Self-Efficacy and Language Anxiety of Theological Seminary Students - Lumintang, Sheline Feranda; Bram, Barli (Universitas Muhammadiyah Mataram, 2024)
This article examined self-efficacy and language anxiety about using English as a foreign language experienced by theological seminary students. Specifically, it explored whether students confident in their language skills would feel less anxious or vice versa. It also aims to discover the strategies students used to overcome language anxiety. A mixed-methods study involving 36 theology students who were asked to complete a questionnaire and 10 of them were also interviewed in depth. The results showed that there was a positive trend, self-efficacy was not always directly or linearly proportional to anxiety levels. However, from the interviews, it was found that some ways help students reduce their anxiety when speaking in a foreign language. Overall, this study highlighted the importance of self-efficacy in foreign language learning, especially for theology students. By increasing students' self-efficacy, theological education institutions can help them by providing facilities or encouragement to achieve better academic performance and be ready to face all challenges in their future ministry tasks.